Penerapan Strategi SEO (Search Engine Optimization) dalam Meningkatkan Penjualan Produk Digital - Saputra, Joni; Afriansyah, M. (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The development of the digital creative industry has encouraged more and more creators to utilize microstock platforms such as Adobe Stock to sell digital animation works. However, high competition and the increasing number of assets often make digital animation products difficult to find by potential buyers. This is a major challenge for creators in increasing the visibility and sales of their work. To overcome this problem, digital marketing strategies such as Search Engine Optimization (SEO) have begun to be implemented as an effort to increase search rankings and product reach. This study aims to analyze the effect of implementing SEO techniques on increasing sales of animation-based digital products on the Adobe Stock platform. In the digital economy era, the microstock marketplace has become a strategic channel for creators in marketing visual assets, but the high level of competition demands the right optimization strategy so that products can be found and purchased. The research method used is a quantitative approach with a one group pretest-posttest design, which is applied to 60 animation assets. The SEO strategy is carried out through metadata optimization, including adjusting the title, selecting relevant and high-value keywords, and contextual descriptions based on search intent. The results showed an increase in sales from 38 to 126 products within three months after SEO was implemented, with an increase of 231.58%. The results of the paired sample t-test showed a p value <0.05, which means the increase is statistically significant. In conclusion, metadata-based SEO has proven effective in increasing the visibility and sales of digital animation products on Adobe Stock. This study recommends that digital asset creators utilize SEO strategies as an integral part of content marketing on microstock platforms.